Review of the current status and development trends of fuel cell air compressor technology - Zheng, Jiageng; Zhang, Taoyuan; Zhang, Wei; Su, Dongjian (БНТУ, 2025)
As the oxygen supply equipment for the cathode reaction in fuel cells, the fuel cell air compressor significantly impacts the reaction efficiency, power density, and miniaturization design of the fuel cell. This article analyzes and summarizes the types, research status, key technology levels, and future development trends of fuel cell air compressors in the current market. Finally, based on air compressor technology, it is predicted that future development will trend towards greater integration and intelligence, as well as a wider operating range.